#Gettinghealthy: The perceived influence of social media on young adult health behaviors. (April 2015) - Vaterlaus, J. Mitchell; Patten, Emily V.; Roche, Cesia; Young, Jimmy A.
Highlights: Perceived social media influence on young adult health is reported. Social media can be a motivator or barrier to exercise. Social media can expand food choices in young adulthood. Young adults use social media to showcase exercise experiences. Abstract: Young adults (18–25 years old) spend a majority of their waking hours with technology and young adulthood is an important developmental time period for establishing lasting health behaviors. Considering the relevance of technology and health during young adulthood the current study explored young adults ( N  = 34) perceptions of social media's (e.g., social networking) influence on their health behaviors (i.e., diet and exercise) using a social ecological framework. Data was collected through eight focus groups and four individual interviews. Three themes were identified through phenomenological qualitative analysis. Young adults perceived that technology could be both a barrier and a motivator for exercise. Social media was also credited with expanding food choices through creating access to a variety of recipes, providing a venue for showcasing the food young adults eat or prepare, and distracting young adults from making positive food choices. Participants also reported that it is common to post statuses or pictures relating to exercise practices on social media during young adulthood. Young adults indicated that these posts could be inspirational or misused, depending on the context. Results are discussed in terms of theory and preliminary implications.